Trends in development of aircraft for regional routes: impact on the european air transportation system - Nõmmik, Allan (Vysoké učení technické v Brně, Fakulta strojního inženýrství, 2019)
The beginning of the twenty-first century in air transportation is characterized by increasing competition between (regular, i.e. not low-cost) airlines, which in its turn affects the low cost airlines by necessitating for them the operating of aircraft with larger seat capacity also on local routes, with the goal of operating the aircraft at lower cost per available seat kilometer. Taking into account the importance of air connections for the regional economy, the local authorities are obligated to support regional airports and impose public service obligations on some routes. This study examines the regional aircraft development after the air transportation market liberalization, while also delving into the background of differences in environments of operation in Europe and United States. To evaluate the regional routes’ equipment competitiveness, this research is focusing on to the regional aircraft fuel consumption which is the considerable factor for airline’s operating costs. Analysis of the differences between operating environments in Europe and the United States is based on an earlier review of the research findings on development of the markets after liberalization, and the role regional aircraft in air transportation system. Also, the comparisons of the profitability and airlines’ strategies in both regions are given. The results provide insights into the main drivers of regional aircraft design and development from the demand’s point of view.
Keywords: Regional aircraft; air transportation system; Public Service Obligations